2002
DOI: 10.1038/sj.mp.4001037
|View full text |Cite
|
Sign up to set email alerts
|

Family-based and association studies of monoamine oxidase A and attention deficit hyperactivity disorder (ADHD): preferential transmission of the long promoter-region repeat and its association with impaired performance on a continuous performance test (TOVA)

Abstract: Monoamine oxidase A (MAO A) is located on the X chromosome and metabolizes biogenic amines including dopamine, norepinephrine and serotonin. A functional promoter-region polymorphism of this gene has been described that has been studied in a number of mental illnesses but not in attention deficit hyperactivity disorder (ADHD). In the current study, we examined the MAO A promoter-region polymorphism initially in 133 triads and observed preferential transmission of the long alleles from 74 heterozygote mothers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
91
5
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 62 publications
9
91
5
1
Order By: Relevance
“…This finding is not inconsistent with previously published results of a significant main effect of the high-activity MAOA genotype on increasing risk for antisocial behavior and ADHD. [59][60][61] Moreover, closer inspection of other G Â E studies involving the MAOA polymorphism reveals similar findings, albeit at marginally significant levels. 3,6,7 For instance, Foley et al 6 found a nonsignificant trend (P < 0.14) for the high-activity MAOA allele increasing risk for conduct disorder; after adjusting for the interaction between the MAOA polymorphism and maltreatment, the main effect became significant (P = 0.04).…”
Section: Discussionsupporting
confidence: 58%
“…This finding is not inconsistent with previously published results of a significant main effect of the high-activity MAOA genotype on increasing risk for antisocial behavior and ADHD. [59][60][61] Moreover, closer inspection of other G Â E studies involving the MAOA polymorphism reveals similar findings, albeit at marginally significant levels. 3,6,7 For instance, Foley et al 6 found a nonsignificant trend (P < 0.14) for the high-activity MAOA allele increasing risk for conduct disorder; after adjusting for the interaction between the MAOA polymorphism and maltreatment, the main effect became significant (P = 0.04).…”
Section: Discussionsupporting
confidence: 58%
“…A high rate of similarity between the carrier state of the parents and their children was also observed by others, (28) but inheritance of risk alleles for ADHD is a complex process as there seems to be a preferential transmission of paternal over maternal alleles (28,29).…”
Section: Discussionsupporting
confidence: 67%
“…30 Dysregulation of monoamine pathways has long been implicated as one of the mechanisms involved in the etiology of ADHD. Several groups [31][32][33][34][35][36] have set out to test whether MAOA confers risk for ADHD, however, definite conclusion has not yet been received. Our data may serve as a support for previous positive reports of linkage/association for MAOA, especially in Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%